APPROACHES TO THE TEACHING FOREIGN LANGUAGES TO ADULTS - Abdugopporova Odinaxon Hoshimjon qizi , (TADQIQOTLAR.UZ, 2024)
Abstract: The article deals with the main modern approaches to teaching adults foreign languages. Each approach is characterized, its advantages and disadvantages are stated. Special attention is paid to teaching foreign languages at non-linguistic high schools. The author comes to the conclusion that only combining various approaches and using different methods of teaching it is possible to develop students’ linguistic competence and their communicative abilities.